Město jako areál revoluce. Sabinovy poslední romány o revoluci 1848 - Jiří Štajf (Theatrum Historiae)
The topic is analyzed on the basis of the last novels by Karel Sabina “Král Ferdinand a jeho doba. Původní román z nejnovějších časů“ [“King Ferdinand and His Period. The Original Novel of the Latest Times”] (1875) and “1848: Předbřeznoví revoluční bouřliváci v Rakousku” [“1848: Pre-March Revolutionary Rebels in Austria“] (German original 1876, Czech translation 1927). The emphasis is put on the way the author, a former “revolutionary rebel”, draws the influence of the bloody street battle participants` experience on the changes in their action motivation.